2009
DOI: 10.1370/afm.1051
|View full text |Cite
|
Sign up to set email alerts
|

Early Abortion in Family Medicine: Clinical Outcomes

Abstract: PURPOSE Clinical innovations have made it more feasible to incorporate early abortion into family medicine, yet the outcomes of early abortion procedures in this setting have not been well studied. We wished to assess the outcomes of fi rsttrimester medication and aspiration abortion procedures by family physicians. METHODS RESULTSThe rate of successful uncomplicated procedures for medication was 96.5% (95% confi dence interval [CI], 95.5%-97.0%) and for aspiration was 99.9% (CI, 99.3%-1). Adverse events and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…In another study conducted by Thaker et al 12 70.2% patient had incomplete abortion and 10.8% had failed abortion. In the study conducted by Bennett et al, 13 medical abortion using correct regimen of mifepristone and misoprostol was associated with high success rate of 96.5%, incomplete abortion as 1.2%, failed abortion as 1.45% and missed ectopic pregnancy as 0.08%.…”
Section: Discussionmentioning
confidence: 94%
“…In another study conducted by Thaker et al 12 70.2% patient had incomplete abortion and 10.8% had failed abortion. In the study conducted by Bennett et al, 13 medical abortion using correct regimen of mifepristone and misoprostol was associated with high success rate of 96.5%, incomplete abortion as 1.2%, failed abortion as 1.45% and missed ectopic pregnancy as 0.08%.…”
Section: Discussionmentioning
confidence: 94%
“…3 In addition, a prospective observational study at 5 family medicine sites, including 4 residency practices, found a success rate of 96.5% for early medical abortion. 8 There was one ruptured ectopic pregnancy in the family medicine group and one pulmonary embolus in the specialized clinic group. Both of these outcomes are secondary to pregnancy and should not be considered evidence that medical abortion is unsafe in either setting.…”
Section: Discussionmentioning
confidence: 99%
“…4 Family medicine sites have been involved in medical abortion research in the United States since the outset and several published studies have demonstrated good outcomes for medical abortion performed in family medicine settings. [5][6][7][8] (In patient education materials, we used the wording "medication abortion" to make it clear to patients that the abortion is caused by a pill; however, the convention used in the medical literature has been to call it "medical abortion," so to be consistent with the published literature we have used that term here.) No published studies have compared medical abortion outcomes in the family medicine setting versus outcomes in specialized reproductive health clinics.…”
mentioning
confidence: 99%
“…3 In a study by Bennett I.M et al, of 1309 patients 96.5% had a complete abortion. 8 In a study by Ashok P.W et al, out of 1961 subjects, 1912 had a complete abortion with no need of surgical intervention. Thus the success rate was 97.5%.…”
Section: Side Effectsmentioning
confidence: 99%